2014
DOI: 10.1242/dmm.015040
|View full text |Cite
|
Sign up to set email alerts
|

RUNX2 in subtype specific breast cancer and mammary gland differentiation

Abstract: RUNX2, a master regulator of osteogenesis, is oncogenic in the lymphoid lineage; however, little is known about its role in epithelial cancers. Upregulation of RUNX2 in cell lines correlates with increased invasiveness and the capacity to form osteolytic disease in models of breast and prostate cancer. However, most studies have analysed the effects of this gene in a limited number of cell lines and its role in primary breast cancer has not been resolved. Using a human tumour tissue microarray, we show that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…RUNX2 establishes a molecular program that opposes ERα signaling in both the normal and transformed settings (Chimge and Frenkel 2013;McDonald et al 2014). In support of these studies, using computational STRING analysis, we identified interactions between RUNX2 and ERα, including established tamoxifen resistance genes (Fig.…”
Section: Identification Of Mrnas Highly Dependent On Overexpression Osupporting
confidence: 60%
“…RUNX2 establishes a molecular program that opposes ERα signaling in both the normal and transformed settings (Chimge and Frenkel 2013;McDonald et al 2014). In support of these studies, using computational STRING analysis, we identified interactions between RUNX2 and ERα, including established tamoxifen resistance genes (Fig.…”
Section: Identification Of Mrnas Highly Dependent On Overexpression Osupporting
confidence: 60%
“…Runx1 has been shown to be the most abundantly expressed among all Runx genes in murine mammary epithelial cells (MMECs) , with its mRNA more elevated in the basal compared to the luminal compartment , while its protein is detected in both lineages of the murine mammary gland and the human breast epithelium (http://www.proteinatlas.org/). Nevertheless, RUNX1 expression seems to be very dynamic throughout the development of the organ, reaching a peak at virgin and involution, while decreasing at mid‐gestation and lactation, when it seems lost by alveolar luminal cells, yet retained by myoepithelial cells .…”
Section: Runx1 and Its Interplay With The Oestrogen/er Signalling Patmentioning
confidence: 99%
“…Although this article has focused on RUNX1, it is important to mention the other RUNX genes ( RUNX2 and RUNX3 ) and certain parallels and distinctions within the tissues described above. Akin to Runx1 , expression of Runx2 fluctuates during different physiological stages of the murine mammary gland and is enriched in the basal compartment, albeit at a lower extent than Runx1 . Indeed, RUNX2 seems to have a central role during the development of the organ, as suggested by its function in mammary stem cells and the impaired growth of the mammary epithelial tree shown in mouse models of Runx2 deletion and overexpression .…”
Section: The Runx1 ‘Siblings’ In Female‐related Cancersmentioning
confidence: 99%
“…RUNX1 is differentially expressed during physiological stages of mammary gland development and exhibits a spatiotemporal expression pattern. The highest levels are observed in virgin and early‐pregnant glands and decrease in late pregnancy and during lactation (McDonald et al, ; Rooney et al, ; van Bragt et al, ). Compared with cells of the luminal lineage, RUNX1 is expressed at higher levels in basal progenitor cells (McDonald et al, ; van Bragt et al, ).…”
Section: Runx1 In Mammary Gland Developmentmentioning
confidence: 99%
“…The highest levels are observed in virgin and early‐pregnant glands and decrease in late pregnancy and during lactation (McDonald et al, ; Rooney et al, ; van Bragt et al, ). Compared with cells of the luminal lineage, RUNX1 is expressed at higher levels in basal progenitor cells (McDonald et al, ; van Bragt et al, ). As RUNX1 expression is lost from differentiated alveolar luminal cells, it has been speculated that a reduction in RUNX1 expression is necessary for milk production and secretion (van Bragt et al, ).…”
Section: Runx1 In Mammary Gland Developmentmentioning
confidence: 99%